The role of digital media in promoting cultural exchange, the language of effective dialogue, and its support for peaceful coexistence on Instagram in the Kingdom of Bahrain (The International Journal of Educational Sciences and Arts, 2025)
The study examines the role of digital media in promoting cultural exchange, the language of effective dialogue, and its support for peaceful coexistence in the Kingdom of Bahrain. It also examines the effectiveness of the Instagram platform in shaping this interaction between individuals and its impact in supporting peaceful coexistence. The study aims to identify the nature of digital media and its impact in promoting cultural exchange and dialogue. It also explores the ability of the Instagram platform to enhance communication between individuals and support peaceful coexistence among members of Bahraini society. The descriptive survey approach was used, and the available sample, consisting of (52) individuals from Bahraini society, was selected. (29) males and (23) females were selected through questionnaire analysis and interviews. The study reached several conclusions, the most important of which is that increased exposure to Instagram contributes to enhancing cultural exchange, fostering dialogue among individuals, and supporting peaceful coexistence among members of Bahraini society. It also recommended the need to pay attention to the importance of digital media and its various means, and to encourage more scientific research that encourages the building of more tolerant, open, and understanding societies within Bahraini society.
Keywords: Digital media; Cultural exchange; Dialogue; Peaceful coexistence; Instagram platform; Kingdom of Bahrain